Have Not Been the Same : the CanRock Renaissance 1985-1995. - Barclay, Michael, 1971- (ECW Press, 2011)
Capturing the spirit of Canadian rock from the late 20th century, this history tells the stories of the musicians and bands that made an indelible mark on Canadian culture and the global stage. Regarded by critics and musicians as the definitive history of the era, this massive tome has been updated to include brand-new interviews and up-to-the-present histories of the bands from Canada's homegrown music industry, including Blue Rodeo, the Tragically Hip, Sarah McLachlan, Sloan, Barenaked Ladies, Daniel Lanois, and many others. Rich, extensive first-person interviews pair with a treasure trove.